PERILAKU DINAMIK PLAT LANTAI BERBENTANG PANJANG DENGAN DAN TANPA PENGAKU RANGKA BATANG - MUKHLIS ISLAM (Universitas Bengkulu, 2018)
The aim of this research is to study the effectiveness and the characteristics of structural dynamics of long span RC slab which is stiffened by the addition of steel truss and to verify the numerical analysis results which might be used in the next stage as material of consideration to analyze and design the stiffening method of any prototype or existing structure in need. The experimental works are carried out by using 2 RC slabs with length, width and thickness are 4,6 x 0,96 x 0,05 m respectively, while numerical work shall be carried out by applying structural analysis computer program. The experimental results which are structural dynamic characteristics then will be compared to numerical result.The results of the research show that the behavior of the structure under dynamic loading increased significantly by addition of steel truss, indicated by the increase of structural natural frequency between 15,565% up to 33,33% for several type of truss. The results also show that the average difference between experimental and numerical analysis is 4,503%.